(untitled) (AYUSHDHARA, 2019)
Pama Vyadhi is one of the commonest diseases found in the low socio economic class. Scabies is a contagious skin infection that spreads rapidly in crowded conditions and is found worldwide. Personal hygiene is an important preventive measure and access to adequate water supply is important (W.H.O.). Minimum 60 diagnosed children with Pama (Scabies) were randomly selected for the clinical study and divided into two groups. The sensitivity test of Durvadya Taila and Gama Benzene Hexachloride 1% Lotion with 0.5ml test dose were applied for one hour and effects are observed for next 3hr. Patients were registered for the clinical study after written consent of their parents. In group A out of 30 children, 50% children were completely cured while markedly improvement occurred in 13% children, moderately improvement occurred in 37% children and none of the children were found in mild improvement as well as in unchanged at all group where as in group B out of 30 children 70% children were completely cured while markedly improvement occurred in 17% children, moderate improvement occurred in 13% children and none of the children were found in mild improvement as well as unchanged at all group. Overall effect of therapy was more significant in Group B.